Institutional contamination produced by student waste at the Universidad de las Fuerzas Armadas ESPE Latacunga campus during the may-september 2023 semester - Abril Enriquez, Jordi Alexander; Chicaiza Flores, Joselyn Janeth; Guzmán Calvopiña, Marjorie Brigitte; Quintuña Uribe, Maykol Alexander; Uto Tigasi, Andy Leonel (Multidisciplinar (Montevideo), 2024)
Institutional contamination by student waste at the Universidad de las Fuerzas Armadas ESPE, Sede Latacunga, is of concern due to lack of environmental awareness, inadequate infrastructure and clear recycling policies. The research reveals a strong awareness among students about the importance of separating waste and recycling, although there are challenges in infrastructure and policies. Students perceive recycling as beneficial for the environment and health. Most support the implementation of recycling and waste separation systems. The need for adequate containers and awareness campaigns is highlighted. Health risks associated with hazardous waste are identified. The university should lead changes towards more sustainable practices, promoting recycling infrastructure, waste reduction and local partnerships. Continuous monitoring and evaluation, increased student participation, and clear policies and environmental education programs are recommended